Upaya Teologis Menjaga Kebebasan Berpendapat di Ruang Media Sosial - Tanjung, Gerald Haruman (Jurnal Teologi Berita Hidup, 2025)
Indonesia is a country that adheres to the principle of democracy that guaranteeing freedom of speech for every citizen. Currently, social media has become a public space that enhances citizen’s participation in democracy through opinions on governance and social issues. The state also regulates social media as an effort to uphold its citizen’s freedom of speech. However, looking at existing phenomena and current research shows us that regulation isn't sufficient to prevent the spread of hate speech, fake news, and bullying on social media. This creates fear and threats to freedom of speech in the public sphere. This study looks at John Stuart Mill's perspective on the importance of ethical awareness in each individual, emphasizing that the freedom one possesses should be used to fulfill one's potential without harming others. This awareness is necessary for every social media user in Indonesia, including Christians, to ensure that freedom of speech is preserved in Indonesia.